Characterization and Catalytic Activity of γ-Al2O3-ITB on Methanol Dehydration. Issue 1 (April 2020) - Ardy, A; Rizkiana, J; Gunawan, M L; Susanto, H
Abstract: National Plan on Energy of Indonesia 2017 states that dimethyl ether (DME, CH3 OCH3 ) will be used as partial substitution of LPG for household fuel. Methanol dehydration using a solid catalyst is a common technology to produce DME. In this research, a catalyst γAl2 O3 prepared in our laboratory has been characterized. This catalyst had a surface area of 194.4 m 2 /g, a total pore volume of 0.55 mL/g, and an average pore diameter of 112, 3 A˙. This catalyst had medium and high acidity sites. Activity tests of this catalyst were carried out in a fixed bed reactor at temperatures of 240, 260 and 280°C. The gas flow rates were related to the gas hourly space velocity of 1500, 2142 and 3000 h −1 . Experimentally, the conversions of methanol were closed to that of thermodynamic conversions, i.e about 90% depending on the reaction temperature. The outlet gas was found to contain H2 up to 2% indicating that there were side reactions besides the dehydration of methanol to DME.